Association of socioeconomic factors and body mass index on visual acuity in 7–10-year-old children - Pranav Patel; Javid Mansuri; Vishwa Patel; Arjun Ramani; Jayraj Brahmbhatt (Journal of Clinical Ophthalmology and Research)
Background: Visual acuity (VA) in children aged 7–10 is a significant concern that can impact academic performance, yet 45%–68% of parents do not seek comprehensive eye examinations. Low physical activity is linked to higher body mass index (BMI), affecting children’s VA. In addition, lower socioeconomic status (SES) restricts access to adequate eye care, contributing to poor eye health in children. Aim: This study aims to conduct preliminary eye exams on 7–10-year-old children within 6 months, to measure BMI using the Center for Disease control and prevention (CDC) calculator, estimate guardians’ SES via a standardized tool, to analyze associations between BMI, VA, SES, and VA using statistical methods, and to record the number of guardians who take their children to an ophthalmologist within 28 days for further eye examinations. Setting and Design: The study design involves longitudinal observational study. Materials and Methods: A Longitudinal study with 304 subjects was carried out. Demographic details, BMI, SES, and vision of 7–10-year-old children were assessed. After 28 days, a follow-up for an ophthalmologist visit for an eye examination was done. Statistical Analysis: Spearman’s correlation was used for BMI, VA, and SES, and Chi-square was used for demographical variables. Results: Out of 304 subjects, most subjects had a healthy weight. VA difficulties affected 47.32% of girls, higher than in boys. The BMI-VA correlation was 0.13, whereas the SES-VA correlation was 0.008. 103 out of 128 subjects with VA referrals were provided. The Chi-square P value for BMI category and gender is 0.001. Conclusions: Our study identified a positive correlation between BMI and VA, but the correlation between SES and VA was found to be very weakly positive.